OTRA Based Voltage Mode Third Order Quadrature Oscillator. (29th April 2014) - Pandey, Rajeshwari; Pandey, Neeta; Komanapalli, Gurumurthy; Anurag, Rashika
Abstract : Two topologies of operational transresistance (OTRA) based third order quadrature oscillators (QO) are proposed in this paper. The proposed oscillators are designed using a combination of lossy and lossless integrators. The proposed topologies can be made fully integrated by implementing the resistors using matched transistors operating in linear region, which also facilitates electronic tuning of oscillation frequency. The nonideality analysis of the circuit is also given and for high frequency applications self-compensation can be used. Workability of the proposed QOs is verified through PSPICE simulations using 0.5  μ m AGILENT CMOS process parameters. The total harmonic distortion (THD) for both the QO designs is found to be less than 1%.